2013
DOI: 10.1134/s1063773713080069
|View full text |Cite
|
Sign up to set email alerts
|

Identification of four X-ray sources from the INTEGRAL and Swift catalogs

Abstract: Four hard X-ray sources from the INTEGRAL and Swift catalogs have been identified. X-ray and optical spectra have been obtained for each of the objects being studied by using data from the INTEGRAL, Swift, ROSAT, and Chandra X-ray observatories as well as observations with the RTT-150 and AZT-33IK optical telescopes. Two sources (SWIFT J1553.6+2606 and SWIFT J1852.2+8424) are shown to be extragalactic in nature: the first is a quasar, while the registered X-ray flux from the second is the total emission from t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Based on Chandra and Swift archival data, Halpern (2012a) found pulsations of the X-ray emission with a period P spin ≃ 46.67 s. The broad band spectrum of IGR J22534+6243 obtained with Chandra, Swift and INTEGRAL observatories can be well described by a powerlaw model with a cutoff energy of 25 − 30 keV, slightly higher than usually observed for X-ray pulsars (Lutovinov et al, 2013a). The proposed optical counterpart 2MASS J22535512+6243368 was observed later by Masetti et al (2012a) and Lutovinov et al (2013a), who revealed an optical spectrum typical for an early type star with superimposed Hα, Hβ and HeI emissions at redshift zero. Based on these measurements it was concluded that IGR J22534+6243 is a X-ray pulsar in a Be high mass X-ray binary system.…”
Section: High-mass X-ray Binaries In the Milky Way 71mentioning
confidence: 98%
See 1 more Smart Citation
“…Based on Chandra and Swift archival data, Halpern (2012a) found pulsations of the X-ray emission with a period P spin ≃ 46.67 s. The broad band spectrum of IGR J22534+6243 obtained with Chandra, Swift and INTEGRAL observatories can be well described by a powerlaw model with a cutoff energy of 25 − 30 keV, slightly higher than usually observed for X-ray pulsars (Lutovinov et al, 2013a). The proposed optical counterpart 2MASS J22535512+6243368 was observed later by Masetti et al (2012a) and Lutovinov et al (2013a), who revealed an optical spectrum typical for an early type star with superimposed Hα, Hβ and HeI emissions at redshift zero. Based on these measurements it was concluded that IGR J22534+6243 is a X-ray pulsar in a Be high mass X-ray binary system.…”
Section: High-mass X-ray Binaries In the Milky Way 71mentioning
confidence: 98%
“…2d). These observations allow to classify IGR J22534+6243 as a new X-ray pulsar in a Be high-mass X-ray binary system (Lutovinov et al, 2013a). Other examples of the optical and infrared spectra of high-mass X-ray binaries, discovered by INTEGRAL are shown in Fig.…”
Section: Hard X-ray Sources and Their Identificationmentioning
confidence: 99%
“…In the previous paper (Krivonos et al 2012), we pre- Lutovinov et al 2013b, for details). A number of multi-wavelength follow-up observations were initiated to unveil the nature of these unclassified objects (Karasev et al 2012;Masetti et al 2013;Revnivtsev et al 2013;Zolotukhin & Revnivtsev 2015;Lutovinov et al 2013aLutovinov et al , 2015Tomsick et al 2015Tomsick et al , 2016aClavel et al 2016;Burenin et al 2016;Rahoui et al 2017) which led to the classification of 11 sources (shown by solid red circles in Fig. 1), rising the total survey identification completeness from ∼92% to ∼94%.…”
Section: Introductionmentioning
confidence: 99%
“…Based on Chandra and Swift archival data, Halpern (2012a) found pulsations of the X-ray emission with a period P spin ≃ 46.67 s. The broad band spectrum of IGR J22534+6243 obtained with Chandra, Swift and INTEGRAL observatories can be well described by a powerlaw model with a cutoff energy of 25 − 30 keV, slightly higher than usually observed for X-ray pulsars (Lutovinov et al, 2013a). The proposed optical counterpart 2MASS J22535512+6243368 was observed later by Masetti et al (2012a) and Lutovinov et al (2013a), who revealed an optical spectrum typical for an early type star with superimposed Hα, Hβ and HeI emissions at redshift zero. Based on these measurements it was concluded that IGR J22534+6243 is a X-ray pulsar in a Be high mass X-ray binary system.…”
Section: Discussionmentioning
confidence: 93%